Policy Implementation Performance Related to the Procurement of PRB Drugs in the Subdistrict Primary Healthcare Center Pharmacy and PRB Pharmacy in Central Jakarta Quarter I, II, and III of 2019 - Nardia, Sari Ulfa; Sjaaf, Amal Chalik (UI Scholars Hub, 2021)
Back-Referral Program (PRB) is one way to improve the quality of the health services for BPJS participants in conducting quality control and cost control. The unavailability of pharmacies and drugs for PRB causes the PRB program not to run optimally, thus increasing the catastrophic disease sufferers and absorbing big claims in JKN. This study is qualitative research with a descriptive approach using the method of in-depth interviews and document review. The research informants' criteria were: the elements of the leadership and policy management officers in the DKI Jakarta Provincial Health Office, Central Jakarta Health Office, Central Jakarta BPJS Health Center, Central Jakarta District Health Center, and Central Jakarta PRB Pharmacy. The results showed that the implementation performance was not optimal, which was influenced by policy standards and objectives, resources, communication between organizations, the implementers' attitude, the implementing organization's characteristics, and the economic, social, and politics. Coordination, commitment, and evaluation of activities from the Ministry of Health, BPJS Health, Government Service Goods Procurement Policy Institute, and DKI Jakarta Provincial Health Office are needed in terms of the availability of this PRB drug